Simultaneous Replication of Hydrophilic and Superhydrophobic Micropatterns through Area‐Selective Monomers Self‐Assembly. Issue 17 (22nd August 2016) - Pardon, Gaspard; Haraldsson, Tommy; van der Wijngaart, Wouter
Abstract : Surface energy mimicking is introduced, enabling spontaneous replication of micropatterns (2D and 2.5D) of different surface energies, and enabled by self‐assembly of functional mimicking monomers within a polymer matrix. Replication of surface energies ranging from hydrophilic to superhydrophobic is demonstrated, as well as self‐assembly of picoliter‐droplet arrays on replicated micropatterns consisting of hydrophilic patches in a hydrophobic surface.